DOI: 10.20868/upm.thesis.288
|View full text |Cite
|
Sign up to set email alerts
|

Demanda de espacios naturales para el ocio: modelos de capacidad de acogida perceptual : Aplicación a los parques nacionales de Timanfaya y Ordesa y Monte Perdido

Abstract: Green tourism is a relatively recent phenomenon which made its greatest advances in the last decades of the 20"" century as a new concept of leisure and tourism.(Goj/í/a, 1999). Green tourism or ecotourism can be seen as the addition of the concepts of responsible. sustainable and environmentally educational tourism {Ecotourism Society, 1993; Bucket, 1994; World Tourism Organization, 1998) to Soo's initial definition (1990) of the kind of tourism which had as its specific aim the study, contemplation and enj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From the year 2000 onwards, studies on carrying capacity increasingly gained significance, coinciding with emerging challenges related to the saturation and degradation of heritage sites, declining quality of tourist experiences, and negative social impacts on resident populations (e.g., gentrification, tourismphobia). This trend is evident in the works of García Hernández [10], Peran López [11], Kostopoulou & Kyritsis [12], López-Bonilla & López-Bonilla [13], Maggi & Fredella [14], García Hernández et al [15], Alazaizeh [16], Santos & Pena Cabrera [17], Viñals et al [18,19], Conti [20], Cruz Aragón [21], Becken & Wardle [22], Guo & Chung [23], Milano [24], and Muler González et al [25]. Over the past five years, the literature demonstrated that recreational carrying capacity continues to be a crucial tool in managing natural parks, archaeological sites, and historical centres, as highlighted in the studies of Zubiaga et al [26], Jurišić et al [27], Llausàs et al [28], Raj Sharma & Bisht [29], Bao et al [30], Red de Parques Nacionales [31], Deffinika et al [3], and Santos & Brilha [32], among others.…”
Section: Background and State Of The Artmentioning
confidence: 82%
“…From the year 2000 onwards, studies on carrying capacity increasingly gained significance, coinciding with emerging challenges related to the saturation and degradation of heritage sites, declining quality of tourist experiences, and negative social impacts on resident populations (e.g., gentrification, tourismphobia). This trend is evident in the works of García Hernández [10], Peran López [11], Kostopoulou & Kyritsis [12], López-Bonilla & López-Bonilla [13], Maggi & Fredella [14], García Hernández et al [15], Alazaizeh [16], Santos & Pena Cabrera [17], Viñals et al [18,19], Conti [20], Cruz Aragón [21], Becken & Wardle [22], Guo & Chung [23], Milano [24], and Muler González et al [25]. Over the past five years, the literature demonstrated that recreational carrying capacity continues to be a crucial tool in managing natural parks, archaeological sites, and historical centres, as highlighted in the studies of Zubiaga et al [26], Jurišić et al [27], Llausàs et al [28], Raj Sharma & Bisht [29], Bao et al [30], Red de Parques Nacionales [31], Deffinika et al [3], and Santos & Brilha [32], among others.…”
Section: Background and State Of The Artmentioning
confidence: 82%
“…There is a clear concentration of demand in the months of March, April and May that gathered 66.6% of the average number of visits per year, leading to problems of overcrowding that, however, do not affect the quality of the recreational experience [58,82].…”
Section: Discussionmentioning
confidence: 99%